Prevalence and associated factors of depression among adult refugees in East Africa: A protocol for systematic review and meta-analysis - Abdu Hailu Shibeshi; Abdulkerim Hassen Moloro; Bizunesh Fantahun Kase; Betel Zelalem Wubshet; Abubeker Alebachew Seid (PLoS ONE, 2025)
Introduction Depression is a common mental health problem among adult refugees in East Africa. Refugees in this region face numerous challenges, including mental health issues, with depression being one of the most common and debilitating conditions. However, there is a lack of systematic reviews and meta-analyses that have been conducted to determine the pooled prevalence and associated factors of depression among adult refugees in East Africa. This study aims to assess the prevalence of depression and its associated factors among adult refugees in East Africa through an analysis of pooled data. Materials and methods A comprehensive search of MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO, and African Journals Online (AJOL) will be conducted to identify studies that have reported the prevalence and associated factors of depression among adult refugees in East Africa. A checklist from the Joanna Briggs Institute (JBI) will be used to assess the methodological quality. The search will be limited to studies published in English. Data extraction, critical appraisal, and screening of all the retrieved articles will be conducted by two independent researchers. Statistical analysis will be performed using STATA-17 software packages. The meta-analysis will be conducted using a random-effects model. The heterogeneity of the studies will be assessed using the I2 statistic. The publication bias will be assessed using the funnel plot and Egger’s test. For determinants of depression, an effect size with a 95% confidence interval will be reported. Ethics and dissemination Ethical approval and informed consent are not required as this is a systematic review of existing publications. The final results will be published in a peer-reviewed journal and presented at national and international conferences. PROSPERO registration number: CRD42024496728